A view of reading comprehension in the students of some universities in Nariño, Colombia. - Burbano, Pedro Pablo; Vallejo Chamorro, Paola; Ortega Calpa, Leidy (SATHIRI, 2020)
The quantitative descriptive research guides its outcome around the question: what is the level of English that the students of first and tenth semesters have in the “Reading Comprehension” competition in universities in Pasto? The samples KET (Key English Test) and PET (Preliminary English Test) of the Common European Framework of Reference, CEFR, were used to determinate their English level and the results were that the students of the first and tenth semesters revealed that their level is quite defective, evidenced by being located the first and the second between levels A- and A1. In other words, more than 95% of the students participating in this research were split, their English is deficient.
Keywords: KET test sample; PET test sample; A1 level; A-level